Legal Writing I & II Legal Research and Writing & Introduction to Litigation Practice - Fernandez, Ben (Open textbook library., 2020)
Legal Writing I & II; Legal Research and Writing & Introduction to Litigation Practice contains a brief discussion of all of the topics covered in a law school courses on legal writing, including a typical first semester course on legal research, analysis and writing an objective memorandum, as well as a second semester course on persuasion and writing an appellate brief, motion to dismiss or motion for summary judgment. The discussion focuses on the basics of analogical reasoning and persuasion and leaves out the minutiae. Each topic is taken one step at a time, with each step building on the step before it. The sources of law are presented first, then legal research, and reading and analyzing cases and statutes. The book covers analogizing a case to a fact pattern and marshaling the relevant facts to the elements of a statutory rule next. And then first section of the book concludes with legal citation, CRAC and CREAC, and writing a legal research memorandum. The text also includes a lot of samples and examples of how the author would write a case brief, a legal memoranda and an appellate brief, as well as an appendix with charts, outlines and exercises students can use to practice these skills. Legal Writing I & II; Legal Research and Writing & Introduction to Litigation Practice covers all the skills students need to know to work at a law firm, and everything students have to learn to begin practicing in litigation department of a firm.